(untitled) (Research, Society and Development, 2020)
Drinking water for human consumption has become a scarce and valuable asset, requiring an assessment of its quality for different uses. The objective, therefore, was to verify the quality of groundwater in the municipality of Juazeiro do Norte, from tubular wells operated by CAGECE, in the Rio Salgado basin, under physical-chemical aspects, referring to space / time variation. The parameters were studied in the dry season, referring to 33 CAGECE heritage wells, totaling 124 samples, divided into 4 periods. For the spatial factor, there are significant variations in the levels of 5%, probability in the parameters pH, alkalinity, calcium, chloride, iron, total dissolved solids (STD) and electrical conductivity (EC). “Levels of 1% and 0.1%” were detected in all wells with Nitrate, using the Tukey test. The groundwater mostly presented characteristics of mixed bicarbonate. The water in the municipality was considered potable, but some areas according to the research show signs of contamination in relation to the nitrate and iron parameter, verified in wells traced in this study.